Fostering Teaching Self-Efficacy of Faculty Through Social Learning: A Mixed Methods Study - Franklin, Elizabeth; Bagwell, Jana; Bryant, Lisa; Colson, Sherry (The journal of faculty development, 2025)
Higher education faculty may have confidence in discipline-related skills and professional experience but lack self-efficacy in teaching. Self-efficacy beliefs about teaching relate to positive outcomes for students and faculty. This study examined the impact of a faculty development program based on Social Learning Theory (SLT) on the Teaching Self-Efficacy Beliefs (TSEB) of faculty in an allied health school. Quantitative findings reveal increased TSEB post-program participation, especially in student engagement, classroom management, and instructional strategies. Qualitative themes emphasized strategic, student-focused, and skills-based activities that are scaffolded and sustained. Findings from this mixed methods investigation apply to all faculty, regardless of setting.